KEGIATAN PENELITIAN/KAJIAN UNTUK PENGEMBANGAN SISTEM ADMINISTRASI NEGARA - Idup Suhady1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
Public administration system and professional, accountable apparatus are undoubtedly required to run a good government. The public administration system in Indonesia is broadly known as the Public Administration System of Republic of Indonesia (SANKRI). Research and studies on this matter strive for revitalizing the roles and functions of SANKRI in which values and norms of good governance are incorporated. Being distinctive from others, this type of reasearch and studies is embeded within policy cycle, and takes aim at actions. In addition, it is inclined to be evaluative, contributive, facilitative, collaborative, and feed-back generating. Further more, it holds totality vision, and becomes a guideline for both basic and applied research.